PEMBERDAYAAN IBU RUMAH TANGGA DESA KABONGAN KIDUL MELALUI EKONOMI KREATIF BERBASIS ENTREPRENEURSHIP UNTUK MENINGKATKAN PENDAPATAN EKONOMI KELUARGA - Dewi, Nurma Gupita; Ilhami, Susanti Dwi (Buletin Abdi Masyarakat, 2025)
This community service aims to improve the family economic income in Kabongan Kidul Village through the empowerment of housewives with a creative economy approach based on entrepreneurship. Kabongan Kidul Village faces challenges in optimizing human resource potential, especially housewives, to play an active role in the family economy. This service activity involves entrepreneurship training, which includes enhancing skills, understanding the principles of creative economy, and the right marketing strategies for the products produced. This program is expected to improve the skills of housewives in creating business opportunities, introduce creativity-based business concepts, and have a positive impact on family economics, both in terms of additional income and social empowerment. Furthermore, this program also encourages collaboration among housewives to form supportive and sustainable business networks. Keywords: Creative Economy, Entrepreneurship, Empowerment.